2021
DOI: 10.20525/ijrbs.v10i7.1422
|View full text |Cite
|
Sign up to set email alerts
|

Talent retention strategies for female academics in the higher education sector

Abstract: This study aimed at identifying talent retention strategies for female academics in the higher education sector, paying particular attention to the Sub-Saharan context. Higher education institutions rely on the knowledge, abilities, and skills of their academics in order to keep abreast of the changing nature of higher education globally. These institutions of higher learning are required to be competitive and achieve their strategic goals in order to remain relevant in the sector. Studies have shown that fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Bartels et al (2021), acknowledged similar trend in their study describing the attrition of female employees in academia as a leaky pipeline, which has called for greater concern in the field of human resource management, according to Coetzee & Moosa (2020). Kanyumba and Lourens (2021) attributed the increasing attrition rate to the inability of HE institutions to recruit, retain and promote females in academia. The trend is not only peculiar to the institution researched or higher education generally but goes beyond.…”
Section: Discussionmentioning
confidence: 93%
“…Bartels et al (2021), acknowledged similar trend in their study describing the attrition of female employees in academia as a leaky pipeline, which has called for greater concern in the field of human resource management, according to Coetzee & Moosa (2020). Kanyumba and Lourens (2021) attributed the increasing attrition rate to the inability of HE institutions to recruit, retain and promote females in academia. The trend is not only peculiar to the institution researched or higher education generally but goes beyond.…”
Section: Discussionmentioning
confidence: 93%
“…Several scholars have proposed diverse opinions and solutions to address the retention challenge in South African HEIs. For instance, Kanyumba and Lourens (2021) found that retention strategies include compensation and benefits, succession planning, training and development and career development opportunities. Similarly, Lesenyeho and Schutte (2020) suggest that HEIs redevelop talent management (TM) practices such as compensation and recognition, career development and general institutional practices to address the diverse needs of a new generation of academics.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Lesenyeho and Schutte (2020) suggest that HEIs redevelop talent management (TM) practices such as compensation and recognition, career development and general institutional practices to address the diverse needs of a new generation of academics. The extant literature suggests that most empirical studies on academic retention in South African HEIs focused solely on compensation and benefits, succession planning, training and development and career development opportunities (Kanyumba & Lourens, 2021;Musakuro & de Klerk, 2021;Lesenyeho & Schutte, 2020). However, there is limited empirical research concerning the influence of promotion, work-life balance and employer-employee relationship on academic retention in South African HEIs.…”
Section: Introductionmentioning
confidence: 99%